Bats and rabies in the northwestern region of São Paulo state, Brazil - Casagrande, D. K. A.; Favaro, A. B. B. B. C.; Carvalho, C.; Picolo, M. R.; Lopes, A. P.; Favoretto, S. R.; Campos, A. C. A.; Hernandez, J. C. B.; Lot, M. S.; Albas, A.; Pedro, W. A.; Queiroz, L. H. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
During the two last decades three distinct cycles of rabies were identified in the northwestern region of São Paulo State: the urban cycle characterized predominantly by canine rabies from 1993 to 1997 and the aerial and rural cycles starting in 1998, with the predominance of cases in bats in urban areas and in herbivores. Twenty six bat species were preliminarily reported in this geographical region, including D. rotundus and Diaemus youngi and from 1998 to 2007, a total of 4,035 bat samples were tested for rabies resulting 50 (1.2%) positive cases in nine non-hematophagous species: three Molossidae, five Vespertilionidae and one Phyllostomidae. The aim of the present research was to describe the occurrence of rabies in non-hematophagous bats and the presence of antibodies against rabies virus in vampire bats in the northwest of São Paulo State, during the period from January 2008 to July 2012. Rabies virus was detected in 22 (1.97%) out of 1117 non-hematophagous bats and none of the 190 vampire bats examined. 82% of the bat positive samples was submitted to antigenic and genetic characterization and the variant of D. rotundus was identified in 28% of them. Serum from 125 vampire bats captured in four different shelters were tested for rabies virus neutralizing antibodies and 28% (35/125) resulted negative; 65% (81/125) resulted positive with titer from 0.10 to 0.5UI/ml and 7% (9/125) higher than 0.5UI/ml. Most of vampire bats presenting antibody were female (61%) from a natural shelter located in a tree role. Although no vampire bat was found positive for rabies, four positive cases of rabies transmitted by that specie were detected in the studied region: three bovine cattle and one cat. The presence of high percentage of vampire bats with virus neutralizing antibody indicates a recent exposure to rabies virus, which confirms that, although this geographical area is considered as low or negligible risk for rabies in herbivorous, surveillance measures should be maintained.